Mote: An ancient recipe in Andean kitchens. Experimental and taphonomic analysis - Musaubach, María Gabriela (2020)
Mote or muti is a traditional Andean recipe that can be traced to pre-Hispanic kitchens. This culinary practice consists of boiling maize grains that were previously dried and peeled with lime or plant ashes (nixtamalization). According to early Spanish sources, this dish forms the dietary staple of common people. Currently, this recipe is also prepared with wheat grains, although maize remains the most important ingredient. Given the difficulty to reconstruct past cooking practices, in this opportunity, food processing pathways of mote preparation in Quebrada de Humahuaca (South-central Andes) are presented to generate indicators for its identification in the archaeological record, concerning both plant macro and micro-remains and the culinary equipment used.A combined approach that includes ethnobotany, ethnography, experimentation, and archaeological methodologies led us to recreate mote recipe following both oral cooking traditional knowledge and the practices registered in our visits to traditional kitchens in Quebrada de Humahuaca. Phytolith and starch grains were analyzed to register their transformation through the different stages of the recipe, considering the way nixtamalization affects them and the indicators that would allow us to recognize them in the archaeological record. Regarding the culinary equipment, the different vessels used were registered according to morpho-functional criteria, and use-wear analysis. As a result, we were able to create a reference collection of modified starch grains and phytoliths, caryopsis fragments and general processing residues, as well as use-wear traces in different vessels that will allow us to advance in the recognition of foodways related to mote preparation in the archaeological record.